CONFIRMATORY FACTOR ANALYSIS INSTRUMEN SIKAP SOSIAL SAINS SISWA SMA - Sriyono; Riawan Yudi Purwoko (PROGRAM STUDI PENELITIAN DAN EVALUASI PENDIDIKAN, 2022)
The social attitude toward science has an essential role in supporting the success of learning science, so valid and reliable measuring tools are needed. This study aims to test the validity and construct reliability of the science attitude instrument. The research subjects involved in this study were 220 high school students of class X. The collected data were then analyzed using confirmatory factor analysis (LISREL version 8.80). The results of the research show that the aspects of honesty, discipline, responsibility, tolerance, cooperation, courtesy, and confidence with their indicators can describe the social attitudes of science. The theoretical model of the designed social science attitude variable turned out to be in accordance with the empirical data. The social science attitude instrument developed has a strong validity (> 0.5) with reliability (CR = 0.98). The confidence factor in this social science attitude instrument is the confidence factor, with a loading factor value of 0.72. In contrast, the weakest factor is honesty, with a loading factor value of 0.57.